The evaluation of social media to increase engagement rate, reach and health education: the case for WoW! - Lekota, Feroza (Department of Human Biology, 2023)
Introduction: In 2021, South Africans had a 51.9 percent chance of dying from an NCD. The Western Cape on Wellness (WoW!) program advocates for wellness, through partnership, innovation and policy, including health in communities, worksites and schools. Increasing knowledge and awareness regarding health behaviors and NCD risk factors is an important pathway in preventing and mitigating the problem at hand through a combination of structural and social policy change. Social media provides an unprecedented opportunity and innovative way to provide a solution to the problem. The internet has increasingly become a popular source of health information by connecting individuals with health content, experts, and support. Aim & Objective: To use a social media campaign with expert knowledge to change healthy lifestyle actions and increase health knowledge and engagement in a para-social western cape on wellness social media group. Methods: A mixed methods quantitative and qualitative analysis was undertaken to assess key messages, which were publicly available on the WoW! Facebook group. 60 lifestyle messages were posted on the WoW! Facebook group 5 times a week from Monday through to Friday. Each message was disseminated by a moderator and followed a theme for the day. Three icons were used to measure levels of participant engagement likes, shares, comments. Associated comments were extracted and coded using a codebook based on items from the supportive accountability model and peer social support analysis. The identified search material was reviewed allowing removal of any personally identifying or geographical material in order that that the comments were rendered anonymous. One –way ANOVA was performed to determine whether level of likes, shares and comments differed between posts. One-way ANOVA was performed to determine whether level of engagement differed between post types, with Tukey–Kramer test used to determine post hoc differences. An independent samples t-test was conducted to determine whether total engagement differed between moderator initiated posts and Facebook user-initiated posts. Results: The most common form of engagement was "likes," and engagement was higher for moderator initiated rather than participant-initiated posts. Overall traffic to the page increased over the 3 month period from 1083 WoW! Facebook users to 1300. Likes were the most common and easiest form of engagement (M=7.6, SD 9.8) with comments being the lowest (m=0.81, SD 2.3). The most engaged with and resonative messages were the #transformationthursday posts. Empirically physical activity behaviour and change in eating patterns did increase over time. The 7 main themes that were identified constituted 53.3% (112/210) of all comments in the pre and during campaign analyses. The most prevalent theme was social cohesion and connectedness at 29% (33/112). The least common theme was developing professional communication and organisational support at 4.5% (5/112). Overall, there were more comments before the campaign (n=63), than during (n=49). In terms of Geographical proximity most of the comments and posts came from participants in the Metro (58.3%) and rural districts Paarl (48.3%) and George (40%). A proximal or virtual tie to a place adds connection and thus value to the information. Conclusion: The favourable results of the WoW! Facebook campaign shows promise for future social media-driven health campaigns to educate and prevent lifestyle related chronic conditions. Social media content for knowledge sharing should be created through a well-intentioned process with the support of moderators to facilitate the conversation and drive engagement.